24=-3(t+-24)

Simple and best practice solution for 24=-3(t+-24) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24=-3(t+-24) equation:


Simplifying
24 = -3(t + -24)

Reorder the terms:
24 = -3(-24 + t)
24 = (-24 * -3 + t * -3)
24 = (72 + -3t)

Solving
24 = 72 + -3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '3t' to each side of the equation.
24 + 3t = 72 + -3t + 3t

Combine like terms: -3t + 3t = 0
24 + 3t = 72 + 0
24 + 3t = 72

Add '-24' to each side of the equation.
24 + -24 + 3t = 72 + -24

Combine like terms: 24 + -24 = 0
0 + 3t = 72 + -24
3t = 72 + -24

Combine like terms: 72 + -24 = 48
3t = 48

Divide each side by '3'.
t = 16

Simplifying
t = 16

See similar equations:

| 2(n-52)-22=2 | | 2(t-64)=56 | | 67-z=40 | | 2(s+1)=10 | | 4(s-90)=-50 | | (5x-6)(x^2-4x-1)= | | (4x^2)-47+70=0 | | M-52=27 | | 3(v+2)=12 | | 3(b+1)+1=10 | | 3(z+-15)=-60 | | 25-w=46 | | 16=-2(n+-17) | | m^2-n^2-am-an=0 | | 6-2x=-20 | | 15p+19.96=-14.08+11.3p | | 2(3r-7)-(2+r)= | | -11.4u-3.54+19.2u=8.34+8.9u | | -5.6k-16.61=-4.5k | | -13.03+5.1m=12.3m+10.01 | | -12.2w+16.74=-13.6w-7.2 | | 11.5d=-7.56+10.3d | | -6.5u+18.93=1.18-12.8u-8.08 | | -8.53-5+19.5z=18.1z-19.97 | | 7.82-1.5g=11.8g-16.12 | | -8.53-5+19.5z=18.1-19.97 | | -5s+16+12=-17-10s | | -4b+20=-18-b-19 | | -10j=19-11j | | 5n-6=6n+11 | | 2(22-8)=22+6 | | (z^(-1/2)z^(5/2))/(z^(1/3)) |

Equations solver categories